PENINGKATAN KETERAMPILAN MENULIS TEKS NEGOSIASI MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE CIRC KELAS X IPS 5 SMA NEGERI 4 BUKITTINGGI - Osmimi Osmimi (Yayasan Akrab Pekanbaru, 2018)
The purpose of this research is to describe the improvement of writing skill of negotiation of class X IPS 5 SMA Negeri 4 Bukittinggi. The findings of the study on the results of improving the negotiating text writing skills through the CIRC cooperative learning model of X IPS 5 grade students of SMA Negeri 4 Bukittinggi were carried out well. The percentage of student completeness has increased, namely in the pre-cycle the percentage of completeness as much as 44.5% with an average value of 65.7, in the first cycle after being given treatment to 69.5% with an average value of 76.9, and in the second cycle being 83.4% with an average value of 86.5. Keywords: improvement, negotiation text writing skills, CIRC Cooperative model.